The Routledge handbook of religion, mass atrocity, and genocide
1 online resource.
Keywords: "The Routledge Handbook of Religion, Mass Atrocity, and Genocide explores the many and sometimes complicated ways in which religion, faith, doctrine, and practice intersect in societies where mass atrocity and genocide occur. This volume is intended as an entry point to questions about mass atrocity and genocide that are asked by and of people of faith and is an outstanding reference source to the key topics, historical events and heated debates in this subject area. The 39 contributions to the handbook, by a team of international contributors, span five continents and cover four millennia. Each explores the intersection of religion, faith, and mainly state-sponsored mass atrocity and genocide, and draws from a variety of disciplines. This volume is divided into six core sections: · Genocide in Antiquity and Holy Wars · The Genocide of Indigenous Peoples · Religion and the State · The Role of Religion During Genocide · Post Genocide Considerations · Memory Culture Within these sections central issues, historical events, debates and problems are examined, including: the Crusades; Jihad and ISIS, colonialism, the Holocaust, desecration of ritual objects, politics of religion, Shinto nationalism, attacks on Rohingya Muslims; the Genocide against the Tutsi in Rwanda, responses to genocide; gender-based atrocities, ritualcide in Cambodia, burial sites and mass graves, transitional justice, forgiveness, documenting genocide, survivor memory narratives, post conflict healing and memorialization. The Routledge Handbook of Religion and Genocide is essential reading for students and researchers with an interest in religion and genocide, religion and violence and religion and politics.It will be of great interest to students of theology, philosophy, genocide studies, narrative studies, history, and international relations and those in related fields, such as cultural studies, area studies, sociology and anthropology"--